Analisis Kesalahan Berbahasa pada Karangan Argumentasi Siswa Kelas VII SMP Muhammadiyah Mamuju Sulawesi Barat - A.Muh.Ayyub; Subianto Basri (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
To find out students' understanding or competence in writing argumentative essays, the right way to do this is to classify the types of student errors in essays, especially in the aspects of spelling, diction and vocabulary mastery used. It aims to make students more active in learning with adequate vocabulary mastery, so that they can compose each sentence properly and effectively. From the results of this study, it appears that, in general, class VII 2 students of SMP Muhammadiyah Mamuju still experience difficulties in mastering writing based on the General Guidelines for Indonesian Spelling (PUEBI). These errors can be seen from the number of students who experience writing errors in writing the first word at the beginning of each sentence, the placement of punctuation marks that are not appropriate, the writing of city names using lowercase letters. In addition, there are still students who have difficulty distinguishing di- as an affix and di- as a preposition and the use of conjunctions or connecting words at the beginning of sentences that are not quite right and writing conjunctions with capital letters at the beginning of words.